Nível de estresse em enfermeiros da rede de atenção às urgências e emergências - Pinto, Cleusa Assis (2018)
Today's world is diverse, urgent, technological and immediate. The relation between this fast world and the individuals seems not to have followed a path of adequate physiological adaptation. This immediacy is also present among nursing professionals, especially nurses working in urgency and emergency service, due to the work environment characteristics. Thus, this research aims to evaluate and classify the stress level among the nurses who work in the Mobile Emergency Care Service (SAMU 192), Central Emergency Room and Emergency Care Units in Bauru-SP-Brazil and it is justified because these services require ability and quick decision-making from these nurses. It is a cross-sectional, observational and quantitative study. The 45 nurses qualified for this study were identified regarding marital status, sex, and ethnicity, length of service, scholarity, socioeconomic level and place of work. The Perceived Stress Scale (PSS-14), Simplified Survey of Signs, and Symptoms were used. The Cronbach's alpha value was calculated to assess internal consistency and the Kruskal-Wallis statistic test to verify differences in stress level according to the workplace. The most frequent demographic findings describe the nurse as female, white, married, with specialization and receiving remuneration above the national average of the category. PSS-14 reveals 84% of the participants with low or moderate perception of stress, remaining only 16% with high or very high perception; the mean score for PSS-14 was 21.9. The conclusion is that nurses who working in Urgency and Emergency Carein this defined geographic area present predominantly low or moderate stress levels, without significant differences between the professionals of different care unitsthere are some physical signs and symptoms as a response to stressors, being predominant asthenia and insomnia.